Mass and Energy Balances Basic Principles for Calculation, Design, and Optimization of Macro/Nano Systems - Ashrafizadeh, Seyed Ali (Mechanical Engineering Series,, 2018)
This textbook introduces students to mass and energy balances and focuses on basic principles for calculation, design, and optimization as they are applied in industrial processes and equipment. While written primarily for undergraduate programs in chemical, energy, mechanical, and environmental engineering, the book can also be used as a reference by technical staff and design engineers interested who are in, and/or need to have basic knowledge of process engineering calculation. Concepts and techniques presented in this volume are highly relevant within many industrial sectors including manufacturing, oil/gas, green and sustainable energy, and power plant design. Drawing on 15 years of teaching experiences, and with a clear understanding of students' interests, the authors have adopted a very accessible writing style that includes many examples and additional citations to research resources from the literature, referenced at the ends of chapters. Maximizes student understanding with worked-out problems and solutions, a glossary, and a bibliography of supporting resources; Explains concepts of mass and energy balance applied to engineering systems in a simple and understandable manner without digression into tangential subject areas; Reinforces student understanding with many real life examples from relevant industries; Includes an introduction to exergy.